A Possible Source of Multiple Polarity Reversals of the Polar Magnetic Field during the Maximum Phase of Solar Cycle - Chunlan Jin; Shuhong Yang; Guiping Zhou; Jialiang Hu; Jingxiu Wang (The Astrophysical Journal, 2025)
During the maximum phase of solar activity, it is quite common for the polar magnetic field to undergo multiple polarity reversals. In this study, we aim to provide the likely source of this phenomenon. By analyzing synoptic magnetograms from the Michelson Doppler Imagers on the Solar and Helioseismic Observatory and the Helioseismic and Magnetic Imager on the Solar Dynamics Observatory throughout Solar Cycle 24, we have identified magnetic structures with densely packed fields by setting area and magnetic field thresholds. These structures are then coupled as bipolar magnetic regions (BMRs) by visual recognition, representing the active regions (ARs) composed of positive and negative polarities. In total, we extracted over 700 BMRs during Solar Cycle 24. Interestingly, we discovered that approximately one-third of these BMRs do not conform to Hale's polarity rule or Joy's law and are thus classified as irregular ARs or abnormal ARs. These irregular ARs distribute in various phases of Solar Cycle 24 and play a negative role in the polar field according to the Babcock–Leighton solar dynamo model. Further, our study shifts to the evolution of these irregular ARs with the obvious poleward flux diffusion and reveals that these ARs indeed produce poleward surges of magnetic flux with opposite polarity in the hemisphere. These findings suggest that these irregular ARs result in the fluctuation of the polar field and even the multiple polarity reversals of the polar field when they emerge during solar maximum.